2020
DOI: 10.1007/s11069-020-04400-2
|View full text |Cite
|
Sign up to set email alerts
|

Geographic scale and probabilistic forecasts: a trade-off for protective decisions?

Abstract: This pilot study aimed to examine the impact of varying geographic scales, probabilities of tornado occurrence, and presentation formats within severe weather forecasts on individuals' protective decisions. This pilot was unique in its specific examination of the tradeoff between highly localized geography and higher valued probabilistic threat information in weather-related decision-making. This pilot utilized a 4 (geographic scale) x 12 (probability) x 3 (forecast presentation format) mixed, nested experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Results from a pair of studies suggests that scale may be more relevant when the event is real and personal to the participant. For example, a study focusing on real-world tornado warnings found that larger polygons led to people being less likely to take shelter (Nagele and Trainor 2012) while a study with hypothetical severe weather forecast scenarios found people were more willing to take preparatory action when the warning was impacting a multiregion area rather than a city (Shivers-Williams and Klockow-McClain 2021). The two studies are not directly comparable, but the differences suggest a need for future studies involving scale and local places with which participants are likely to be familiar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from a pair of studies suggests that scale may be more relevant when the event is real and personal to the participant. For example, a study focusing on real-world tornado warnings found that larger polygons led to people being less likely to take shelter (Nagele and Trainor 2012) while a study with hypothetical severe weather forecast scenarios found people were more willing to take preparatory action when the warning was impacting a multiregion area rather than a city (Shivers-Williams and Klockow-McClain 2021). The two studies are not directly comparable, but the differences suggest a need for future studies involving scale and local places with which participants are likely to be familiar.…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to account for this in the study. Past research has shown that even telling participants that they live in a particular location may not be sufficient (Shivers-Williams and Klockow-McClain 2021). Research currently being conducted by the authors is examining whether county borders are relevant to descriptions of personalized risk areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maps supplementing short mock alert messages have the potential to reduce confusion and increase understanding of emerging threats (Sutton & Fischer, 2020), and have been shown to improve comprehension and behavioural compliance intention in a crisis (Liu et al., 2017). Shivers‐Williams and Klockow‐McClain (2020) report maps are only moderately important in decision‐making but having a map to reference during decision‐making was evaluated as equally important by all participants regardless of the warning information they received.…”
Section: Introductionmentioning
confidence: 99%